2023
DOI: 10.3389/fphys.2023.1145973
|View full text |Cite
|
Sign up to set email alerts
|

A comparative review on the well-studied GAT1 and the understudied BGT-1 in the brain

Abstract: γ-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the central nervous system (CNS). Its homeostasis is maintained by neuronal and glial GABA transporters (GATs). The four GATs identified in humans are GAT1 (SLC6A1), GAT2 (SLC6A13), GAT3 (SLC6A11), and betaine/GABA transporter-1 BGT-1 (SLC6A12) which are all members of the solute carrier 6 (SLC6) family of sodium-dependent transporters. While GAT1 has been investigated extensively, the other GABA transporters are less studied and their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 209 publications
0
3
0
Order By: Relevance
“…The detailed analysis of the PSS currents gives information about the initial steps of the transporter cycle and the interaction of the transporter with ions and substrate [22]. The analysis of the decay time constant (τ) of the large transient currents as inrate β and outrate α constants showed that in the presence of betaine (0.1 and 1mM), β of rGAT1 increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed analysis of the PSS currents gives information about the initial steps of the transporter cycle and the interaction of the transporter with ions and substrate [22]. The analysis of the decay time constant (τ) of the large transient currents as inrate β and outrate α constants showed that in the presence of betaine (0.1 and 1mM), β of rGAT1 increased.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been published that betaine might interact with the GABAergic pathway beyond BGT-1 and play a role as a signalling ligand in the CNS [19][20][21]. To investigate the potential modulatory role of betaine, we studied its interaction with GABA transporter 1 (GAT1, slc6a1) [22]. The expression of GAT1 is mainly neuronal, predominantly in the adult frontal cortex, and among all GATs it is the most expressed GAT in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of the PSS currents gives information about the initial steps of the transporter cycle and the interaction of the transporter with ions and substrate [22]. The analysis of the decay time constant (τ) of the large transient currents as outrate α and inrate β constants showed that in the presence of betaine (0.1 and 1mM), β of rGAT1 increased.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that betaine might interact with the GABAergic pathway beyond BGT-1 and play a role as a signalling ligand in the CNS [19][20][21]. To investigate the potential modulatory role of betaine, we studied its interaction with GABA transporter 1 (GAT1, slc6a1) [22]. The expression of GAT1 is mainly neuronal, predominantly in the adult frontal cortex, and among all GATs it is the most expressed GAT in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…It is also closely related to GAT1 (GABA Transporter SLC6A1) and glycine transporters (SLC6A5 and SLC6A9), which belong to the same neurotransmitter and amino acid transporter family ( Castagna et al, 2022 ) and regulate, with other transporters of the family, the homeostasis of the two inhibitory neurotransmitters. These two transporters have been well characterized and studied for their electrical properties by our group ( Pérez-Siles et al, 2012 ; Bhatt et al, 2023 ). Furthermore, they elicit larger transport currents than DAT when expressed in Xenopus laevis oocytes.…”
Section: Introductionmentioning
confidence: 99%